Freezing-then-aging treatment improved the protein digestibility of beef in an in vitro infant digestion model. (15th July 2021) - Lee, Seonmin; Jo, Kyung; Jeong, Hyun Gyung; Yong, Hae In; Choi, Yun-Sang; Kim, Dongjun; Jung, Samooel
Highlights: Freezing had no effect on tertiary structure of myofibrillar protein in beef. Freezing enhanced the cathepsin B activity in beef during aging. Protein degradation was increased in beef with freezing-then-aging treatment. Freezing-then-aging improved the digestive susceptibility of actin. In vitro protein digestibility of beef was improved by freezing-then-aging. Abstract: In vitro protein digestibility of freezing-then-aged beef was investigated in an infant digestion model. The treatments were divided into freezing-then-aging (FA) and aging-only (AO) groups. Carbonyl and total free sulfhydryl contents were the same between both groups for 14-day aging. Freezing had no effect on beef myofibrillar protein tertiary structure. Although caspase-3 activity did not differ, the FA group showed higher cathepsin B activity than the AO group (p < 0.05). The 10% trichloroacetic acid-soluble α-amino content was higher in FA than AO group, on aging day 14 (p < 0.05). Post in vitro digestion of beef aged for 14 days, the FA group had a higher content, than the AO group, of α-amino groups and proteins digested under 3 kDa (p < 0.05). An electrophoretogram of the digesta showed improved digestion of actin in the FA group. Collectively, the freezing-then-aging process enhanced the protein digestibility of beef in this in vitro infant digestion model.